The Correlation between Grammar Usage and Indonesian – English Translation Ability of English Study Program Students - Nurdin, Andini Putri Surya; Syarfi, Muhammad; Erni, Erni (UIR Press, 2024)
Grammar is an important component of a language that contains rules on the sentence structure construction and meaning system of the language. The grammar usage has a contribution in the language learning process, one of which is in translation. This research aimed to discover the correlation between grammar usage and Indonesian – English translation ability of the fourth-semester English Study Program students. The instruments of the research were sentence completion and error recognition questions for English grammar test and Indonesia – English translation essay for translation test. The statistical analysis using Pearson product-moment formula was applied to analyze the correlation between grammar usage and Indonesian – English translation ability of the fourth-semester students. The result of data analysis revealed that the Pearson correlation value r-counted of 0.837 was higher than r-table of 0.320 at the level of confidence 0.05 which meant that alternative hypothesis (Ha) was accepted and of null hypothesis (H0) was rejected. The research findings revealed that there existed a significant correlation between English grammar usage and Indonesian – English translation ability the fourth-semester English Study Program students of Universitas Riau. It is implied that the proficient English grammar students displayed commensurate in Indonesian – English translation ability while those who lack of grammar usage ability found difficulty in translation tasks. This research highlighted the critical role of grammar in shaping translation of the fourth-semester students of Universitas Riau English Study Program.